Analisis Biaya Kualitas Dan Produktivitas Pada Mahasisiwa Universitas Islam 45 - Anisa Putri (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2018)
The aim to be achieved in this study is to analyze the quality and productivity costs of case studies at the Islamic University of 45 Bekasi. The research method used in this study is a qualitative descriptive method. The location of the study was conducted at the Islamic University of 45 Bekasi. The data used is secondary data from the financial statements of Islamic University of 45 Bekasi in the academic year 2013/2014. Methods of data collection using interviews and observation. The highest quality cost discussion results are prevention costs at the cost of seminars and training for lecturers as much as Rp. 450,561,400, -. The lowest quality cost is the assessment fee at the cost of lecturer accreditation of Rp. 1,925,000, -. The percentage of quality costs is 2.1% smaller than the fairness of the total quality costs of 2.5%. The realization of the output of new student admissions was obtained in the 2013/2014 school year as many as 1,339 people. Total students 6,364 people. The study period is more than 4 years and has not graduated as many as 992 people. Failure costs as much as 16% of total students. Realization of financial output was achieved in the amount of Rp. 39,384,232,556, - ​​Input Rp. 35,606,307,800, - used to obtain output. Company productivity is efficient because output is greater than input. Company productivity is effective because the company achieves financial goals by obtaining a surplus of Rp. 3,777,924,756, - The conclusion that can be drawn is that quality costs are able to obtain output in the form of income exceeding its input value so that productivity is efficient and effective and surplus.